Numerical simulation and analysis of mechanized suppression process of seedbed with whole plastic film mulching on double ridges - Dai, Fei; Song, Xuefeng; Zhao, Wuyun; Sun, Bugong; Shi, Ruijie; Zhang, Yang (International Journal of Agricultural and Biological Engineering, 2021)
In order to achieve the construction standard of high mechanized performance of the seedbed with whole plastic-film mulching on double ridges, in this study, the forms of suppression failure were analyzed, and the key factors influencing the suppression performance were determined based on the structure of the seedbed suppression device and its working principles. The discrete element method was adopted for numerical simulation on the suppression process of the seedbed with whole plastic film mulching on double ridges; the parameters during the interaction between the suppression device and seedbed soil were extracted and analyzed, such as contact area, sinkage and horizontal traction resistance trend of press wheels on big ridges and furrows of small ridge. Taking the suppression load on big ridges, suppression load on furrows of small ridge, and advancing velocity of the combined operation machine as the independent variables, qualified rate of suppression as the response value, a mathematical model between the test factors and qualified rate of suppression was established, to explore the influence sequence of the factors on suppression qualified rate. The optimal working parameters of the suppression device were finally obtained: the suppression load on big ridges was 40 N, suppression load on furrows of small ridge was 69.8 N and the machine advancing velocity was 0.98 m/s, and the achieved mean value of suppression qualified rate was 92.6%. Field verification test showed that the mean value of suppression qualified rate was 90.3%, a mere difference of 2.3% compared with the simulation result. The actual operation of the sample machine was basically consistent with the simulation process and could reveal the mechanized suppression operation mechanism of the seedbed with whole plastic film mulching on double ridges, indicating that the established DEM model and its parameter setting were relatively accurate and reasonable.Keywords: seedbed, whole plastic film mulching, double ridges, mechanized suppression, discrete element method, numerical simulation, parameter optimizationDOI: 10.25165/j.ijabe.20211401.5866Citation: Dai F, Song X F, Zhao W Y, Sun B G, Shi R J, Zhang Y. Numerical simulation and analysis of mechanized suppression process of seedbed with whole plastic film mulching on double ridges. Int J Agric & Biol Eng, 2021; 14(1): 142–150.